A whole exome sequencing study to identify rare variants in multiplex families with alcohol use disorder - Hill, Shirley Y.; Hostyk, Joseph (Frontiers in Psychiatry, 2023)
Background Alcohol use disorder (AUD) runs in families and is accompanied by genetic variation. Some families exhibit an extreme susceptibility in which multiple cases are found and often with an early onset of the disorder. Large scale genome-wide association studies have identified several genes with impressive statistical probabilities. Most of these genes are common variants. Our goal was to perform exome sequencing in families characterized by multiple cases (multiplex families) to determine if rare variants might be segregating with disease status. Methods A case-control approach was used to leverage the power of a large control sample of unrelated individuals (N = 8,983) with exome sequencing [Institute for Genomic Medicine (IGM)], for comparison with probands with AUD (N = 53) from families selected for AUD multiplex status. The probands were sequenced at IGM using similar protocols to those used for the archival controls. Specifically, the presence of a same-sex pair of adult siblings with AUD was the minimal criteria for inclusion. Using a gene-based collapsing analysis strategy, a search for qualifying variants within the sequence data was undertaken to identify ultra-rare non-synonymous variants. Results We searched 18,666 protein coding genes to identify an excess of rare deleterious genetic variation using whole exome sequence data in the 53 AUD individuals from a total of 282 family members. To complete a case/control analysis of unrelated individuals, probands were compared to unrelated controls. Case enrichment for 16 genes with significance at 10–4 and one at 10–5 are plausible candidates for follow-up studies. Six genes were ultra rare [minor allele frequency (MAF) of 0.0005]: CDSN, CHRNA9, IFT43, TLR6, SELENBP1, and GMPPB. Eight genes with MAF of 0.001: ZNF514, OXGR1, DIEXF, TMX4, MTBP, PON2, CRHBP, and ANKRD46 were identified along with three protein-truncating variants associated with loss-of-function: AGTRAP, ANKRD46, and PPA1. Using an ancestry filtered control group (N = 2,814), nine genes were found; three were also significant in the comparison to the larger control group including CHRNA9 previously implicated in alcohol and nicotine dependence. Conclusion This study implicates ultra-rare loss-of-function genes in AUD cases. Among the genes identified include those previously reported for nicotine and alcohol dependence (CHRNA9 and CRHBP).